ANALISIS PEMAHAMAN MATERI MENGGUNAKAN GOOGLE COLABORATORY PADA MATA PELAJARAN INFORMATIKA KELAS X DI SMAN 5 KOTA SERANG - Ayu Trisnawati; Dewi Surani; Bunga Sri Kurniawan; Ari Fidriyanto (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
The development of technology in the world of education is very helpful, especially in improving the quality of learning, especially in informatics subjects at SMAN 5 Serang City. The aim of this research is to describe the analysis of material understanding using Google Collaboratory in informatics subjects at SMAN 5 Serang City in classes X 7 with a total of 50 students and X 10 with a total of 50 students so there are a total of 100 students. The type of method of this research is descriptive qualitative, this research is to describe understanding of the material using Google Collaboratory in the informatics subject, data analysis material with the Python programming language sub-material.